Thoracic Presentations of Small Round Blue Cell Tumors - Chang, Annalice (J Clin Imaging Sci, 2016)
The term “small round blue cell” is frequently used as a cursory radiologic pathological correlation of aggressive tumors throughout the body. We present a pictorial essay of common and uncommon subtypes of small round blue cell tumors in the chest illustrating the characteristic radiologic findings of each lesion. In addition, we review the pathologic findings of each tumor subtype with characteristic hematoxylin- and eosin-stained photomicrographs and immunohistochemical and molecular studies. Represented tumors include small cell carcinoma, Ewing sarcoma, extranodal marginal zone B-cell lymphoma, embryonal rhabdomyosarcoma, desmoplastic small round cell tumor, and posttransplant lymphoproliferative disorder. Understanding and ability to recognize these lesions are essential to broaden the radiologist's differential diagnosis and help guide patient care.